Determination of physico-chemical properties and heavy metal contamination of batik wastewater from textile workshop, UMK Bachok campus - Dee, Koh Han (2017)
Batik industry is the biggest textile industry in the South East of Asia, especially in Malaysia. It provides the handicraft products that contribute greatly to the economy for the Malaysia, but at the same time, it affects human health, aquatic lives and environment. This research investigates the physico-chemical properties and heavy metal concentration of batik wastewater discharge from the textile workshop, UMK Bachok Campus. Physical parameters such as total dissolved solids, temperature and turbidity and chemical parameters such as pH, chemical oxygen demand, total suspended solid and ammoniacal nitrogen were also investigated. Furthermore, the concentrations of selected heavy metals of the discharged batik wastewater were determined and compared to the Environmental Quality (Industrial Effluents) Regulations 2009 under the Environmental Quality Act 1974. A total of five heavy metals were investigated in this research including zinc, manganese, aluminum, nickel and copper. The concentration of the heavy metals was determined by colorimetric method. The results obtained showed that some of the physico-chemical parameters are exceeding the acceptable conditions for discharge of industrial wastewater for mixed wastewater of standard B set by the Environmental Quality (Industrial Effluents) Regulation 2009 under the Environmental Quality Act 1974. Among them are chemical oxygen demand, total suspended solid, total dissolved solid,turbidity and pH of the batik wastewater. While for the selected heavy metals, all of them are within the acceptable conditions for discharge of industrial wastewater for mixed wastewater of standard B set by the Environmental Quality (Industrial Effluents) Regulation 2009. Therefore, all the concentrations of physico-chemical and heavy metal that exceed the standard should be reduced before discharged.